Polymorphism of Sikumbang Jonti ducks Growth Hormone (GH) Gene using PCR-RFLP Methods - Teguh Rafian; Yurnalis Yurnalis; Husmaini Husmaini; Firda Arlina (AGRITROPICA : Journal of Agricultural Sciences, 2023)
This research aimed to identify polymorphism of the GH gene in Sikumbang Jonti ducks using the PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) method as a candidate for genetic marker selection. This research used 123 blood samples of male and female Sikumbang Jonti ducks. The ducks were eight weeks old and kept intensively at the UPT Fakultas Peternakan Universitas Andalas. Blood samples of Sikumbang Jonti ducks were taken through the brachial vein as much as ± 2 mL. The Genomic DNA Purification Kit (Promega) protocol isolated DNA from blood samples. A pair of primers F amplified the total DNA: 5'-GGA CAG CCT GAG GAA AGA GT-3 'and R: 5'-GTG GAA GGT GGG GAG ACT TC-3', which produced a fragment region of the GH gene exon 3 with a cut region of part intron two and part intron 3 with a primary length of 833 bp. The amplified product was restricted by the enzyme TasI which recognizes the cutting site (↓AATT). Based on the restriction results, two (2) genotypes were obtained, namely homozygous (-/-) as many as four (4) and homozygous (+/+) as many as 119. The analysis of restriction products included the allele frequency, namely the allele (+) of 0.98 and the allele (-) of 0.02, and genotypes frequency of homozygous (-/-) of 0.03 and homozygous genotypes (+/+) of 0.97. The diversity of the GH gene is in the Hardy-Weinberg equilibrium. Based on the research results, it can be concluded that there is diversity in the GH gene of the Sikumbang Jonti duck, and it is in the Hardy-Weinberg equilibrium, so it can be used as a candidate for the genetic marker of ducks.